A validation and application of the L2 motivational self system among Chinese learners of English - Magid, Michael (2011)
This thesis consists of two mixed-methods studies: a validation study and an application study of Dörnyei's (2009a) L2 Motivational Self System with participants from China. The quantitative part of the validation study involved 1,154 Chinese middle school and university students from mainland China and the follow-up qualitative study consisted of ten Chinese university students at a British university from mainland China. Structural equation models and correlational analyses validated the L2 Motivational Self System in China. The issues of family, face, responsibility, and pressure clarified the motivational role of the Chinese family and explained the main relationships in the system. Differences in the motivational orientation of the two sub-groups demonstrated the ability of the system to represent different age groups. The application study involved an intervention programme that I developed at a British university in order to motivate my participants to put more time and effort into learning English by enhancing their vision of their Ideal L2 self. The programme contained 31 participants who were international students from China. The programme made most of the participants more motivated to learn English and all of them more confident in their English. There was a significant increase in the strength of the participants' Ideal L2 self as a result of the programme. The vision of the participants' Ideal L2 self and their goals for learning English became more clear and specific due to the programme. Motivation and confidence were found to mutually affect each other. Most of the participants' imagination improved as a result of the programme. They became more proficient in English, more aware of the importance of English in their lives, and their attitudes toward learning English became more positive due to the programme.